2019
DOI: 10.1177/1099636219856556
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory response and acoustic radiation behavior of laminated functionally graded composite plates in thermal environments

Abstract: The present study is concerned with vibro-acoustic behavior analyses of laminated functionally graded carbon nanotube reinforced composite plates based on Reddy’s higher order shear deformation theory. Four types of carbon nanotubes distributions along the plate thickness are considered, which include uniformly distributed and three other functionally graded distributions. Governing differential equations are derived by means of Hamilton’s principle. The sound pressure and radiation efficiency are calculated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…22 The effects of the CNT volume fraction and carbon nanotubes distribution on vibro-acoustic characteristics of laminated FG-CNT composite plates under various temperatures were studied. 23 The effect of temperature profile on dynamic characteristics of aluminum silicon carbide metal matrix composite was examined. 24 Non-uniform edge loading effects on dynamic characteristics of FG-graphene composite plate were investigated and found that graphene nanoplatelets distribution and volume fraction significantly altered the resonant amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…22 The effects of the CNT volume fraction and carbon nanotubes distribution on vibro-acoustic characteristics of laminated FG-CNT composite plates under various temperatures were studied. 23 The effect of temperature profile on dynamic characteristics of aluminum silicon carbide metal matrix composite was examined. 24 Non-uniform edge loading effects on dynamic characteristics of FG-graphene composite plate were investigated and found that graphene nanoplatelets distribution and volume fraction significantly altered the resonant amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they calculated the sound pressure and radiation efficiency and carried out a numerical comparison with available literature results to confirm the presented model’s validity. 37 Wen et al 38 proposed an ultra-light-weight sandwich panel with a closed octahedral core, which demonstrated the excellent acoustic property of sound transmission loss as well as outstanding mechanical performance. Hasheminejad and Jamalpoor proposed a three-dimensional analytical model developed to control sound transmission through an acoustically baffled supported hybrid smart double sandwich panel partition of rectangular planform.…”
Section: Introductionmentioning
confidence: 99%
“…Qu and Meng [39] developed a numerical model for the nonlinear vibro-acoustic analysis of a skin–core debonded sandwich plate immersed in an infinite fluid. Fu et al [40] analyzed the vibro-acoustic behavior of laminated FG carbon nanotube reinforced composite plates based on Reddy’s higher order shear deformation theory. In despite of the abovementioned investigations, however, there is only little research on the vibro-acoustic coupling characteristics of FG honeycomb sandwich plates with negative Poisson’s ratio.…”
Section: Introductionmentioning
confidence: 99%